Borderline personality features in depressed or anxious patients. (30th July 2016) - Distel, Marijn A.; Smit, Johannes H.; Spinhoven, Philip; Penninx, Brenda W.J.H.
Abstract: Anxiety and depression frequently co-occur with borderline personality disorder. Relatively little research examined the presence of borderline personality features and its main domains (affective instability, identity problems, negative relationships and self-harm) in individuals with remitted and current anxiety and depression. Participants with current ( n =597) or remitted ( n =1115) anxiety and/or depression and healthy controls ( n =431) were selected from the Netherlands Study of Depression and Anxiety. Assessments included the Personality Assessment Inventory – Borderline Features Scale and several clinical characteristics of anxiety and depression. Borderline personality features were more common in depression than in anxiety. Current comorbid anxiety and depression was associated with most borderline personality features. Anxiety and depression status explained 29.7% of the variance in borderline personality features and 3.8% (self-harm) to 31% (identity problems) of the variance in the four domains. A large part of the variance was shared between anxiety and depression but both disorders also explained a significant amount of unique variance. The severity of anxiety and depression and the level of daily dysfunctioning was positively associated with borderline personality features. Individuals with a longer duration of anxiety and depression showed more affective instability and identity problems. These findings suggest that patients with anxiety and depression may benefit from an assessment of personality pathology as it may have implications for psychological and pharmacological treatment. Highlights: Borderline personality features are more common in depression than in anxiety. Anxiety and depression explain a significant amount of variance in borderline features. Anxiety and depression explain 3.8–31% of the variance in the four borderline domains. Variance in borderline features is partly shared and partly unique for anxiety and depression. Borderline features are associated with greater anxiety and depression severity.